Current challenges and future prospect of biomass cooking and heating stoves in Asian Countries - Ahmad, Riaz; Ilyas, Hafiza Nabila; Li, Bin; Sultan, Muhammad; Amjad, Muhammad; Aleem, Muhammad; Abbas, Adnan; Imran, Muhammad Ali; Riaz, Fahid (Frontiers in Energy Research, 2022)
The utilization of biomass for cooking and heating is old, occurring from the early stages of human evolution because of its wide and easy availability. In Asia, a majority of the population is dependent on solid biomass for cooking and heating applications. Biomass cookstove produces emissions like carbon monoxide (CO), and particulate matter with aerodynamic diameter ≤2.5 μm (PM2.5) which are dependent on the classifications and characteristics of fuel used in stoves. These emissions trigger many health risks because of the utilization of traditional cookstoves (TCS) which have less thermal efficiency. The literature contains a considerable amount of information on biomass cookstoves; however, it is dispersed particularly in Asian countries. In this principle, this paper gives an overview of available literature on biomass cookstoves for cooking and heating in Asian countries which are involving Bangladesh, China, India, Mongolia, Nepal, Pakistan, Sri Lanka, and Laos. This paper covers a detailed discussion on various aspects of biomass cookstoves: history, classification, fuel characteristics, health risks, design criteria, the scenario in selected Asian countries, thermal efficiency and emission comparison, and barriers to dissemination of improved biomass cookstoves (ICS). Learning from the review and comparison made conclude that the ICS has better thermal efficiency, and lesser emissions, as well as health risks but, have some potential barriers to dissemination.